Application of "three lines and one plane" as anatomic landmarks in laparoscopic surgery for bile duct stones. Issue 16 (April 2018) - Wang, Lei; Zhou, Dachen; Hou, Hui; Wu, Chunli; Geng, Xiaoping
Abstract : Abstract: To investigate the clinical application ofthe "three lines and one plane" concept as the anatomic landmarks during laparoscopic common bile duct exploration (LCBDE). From January 2014 to February 2017, 148 cases of LCBDE performed in the General Surgery Department of the 2nd affiliated Hospital of Anhui Medical University were recruited, and analyzed in this study. "Three lines and one plane" was applied as anatomical landmarks during LCBDE, and the perioperative clinical outcomes were analyzed. No serious operational complications occurred in all the patients in this study. Two cases (1.4%) was converted to open operation. Two other cases (1.4%) suffered post-operative bile leakage and were cured by conservative treatment. All patients recovered uneventfully. Anatomical landmarks of "three lines and one plane" is benefit in helping surgeons to build a three-dimensional (3D) anatomical construction, and avoiding the operative injury of the bile duct, and vessels.